1998
DOI: 10.1007/s007020050037
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the cerebrospinal fluid level of β-endorphin and substance P

Abstract: To evaluate the early age-related changes in neuropeptides, we have measured the cerebrospinal fluid (CSF) levels of beta-endorphin and substance P in young patients over a range of ages. Specimens of CSF were obtained from 39 neurologically normal children, aged 1 month to 10 years of age, and in 9 adult controls. CSF levels of both neuropeptides were observed to peak during the first year of life, and showed a negative correlation with increasing age. A significant positive correlation was observed between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…There are only a few studies on CSF β-endorphin level in children. Echenne et al (1991;Nagamitsu et al, 1998) measured CSF β-endorphin levels in 15 young girls with Rett syndrome and reported a mean value of 6.65 ± 3.45 pmol/L which was also higher than the value obtained in our study.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…There are only a few studies on CSF β-endorphin level in children. Echenne et al (1991;Nagamitsu et al, 1998) measured CSF β-endorphin levels in 15 young girls with Rett syndrome and reported a mean value of 6.65 ± 3.45 pmol/L which was also higher than the value obtained in our study.…”
Section: Discussioncontrasting
confidence: 89%
“…It may thus be due to chance. However, CSF levels of β‐endorphin have been observed in CNS infections to peak during the first year of life with a negative correlation with increasing age (Nagamitsu, ; Nagamitsu et al., ). For ethical reasons, CSF β‐endorphin was not determined in the controls in this study.…”
Section: Discussionmentioning
confidence: 99%
“…That is, age had no inXuence on the eVect of exercise on E levels (HatWeld et al 1987;Struder et al 1999). A negative correlation exists between E level of the CSF and advancing age (Nagamitsu et al 1998). Experience with exercise-i.e.…”
Section: Physical Activity and Agementioning
confidence: 92%
“…Notably, our healthy controls were markedly younger, and one study has described that CSF‐BE decreases with age [27]. However, other studies have failed to confirm this age effect on CSF‐BE [24,28–30]. At any rate, our multivariate data analysis showed that even when taking age into account, group membership was still a significant predictor for the levels of CSF‐BE.…”
Section: Discussionmentioning
confidence: 58%